FORMULATION AND PHYSICAL CHARACTERISTICS OF DETAM II SOYBEAN (GLYCINE MAX (L.) MERR) TABLET WITH VARIOUS CONCENTRATION OF SILICON DIOXIDE AND MAGNESIUM STEARATE - Yulia, Rika; Pradana, Aditya Trias; Sie, Sylvia Silvanus; Suri, Fitria Atika (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This research was conducted to obtain several formulation and evaluate the physical characteristics of the soybean Glycine max (L.) Merr Detam II variety tablets. Methods: Detam II varieties of soybean (G. max (L.) Merr.) were cleaned and grinded into 30 mesh-sized powder. Weighed soybean powder and internal phase of excipients (based on the formula) mixed by a Y-cone mixer until homogeneous, and then continue with dry granulation process. Granules formed, then sieved into 16 mesh size, and then, the characteristics examined. Dried granules then mixed with magnesium stearate and silicon dioxide using a drum mixer and compressed into tablets. Physical characteristics of tablets measured at 0, 4, 7, 14, 21, and 28 days. Results: Evaluation was done for particle size distribution, moisture content (MC), flow properties, weight uniformity, friability, hardness, and disintegration time. Dry granulation was the best method to improve the characteristics of soybean powder with poor compressibility, poor flowability, and hygroscopic. Flow properties of the granules became better for Formula II and III by adding the concentration of silicon dioxide. The formulas also showed the good uniformity of weight, size, MC, friability, and disintegration time. Reducing the lubricant until 0, 5% of the formula made differences in friability, hardness, and disintegration time better than another formula. Conclusion: The result of this research indicates that differences in silicon dioxide and magnesium stearate composition of the formula can affect the physical characteristics of soybean (G. max (L.) Merr.) tablets. Â